Muscle energy technique and static stretching in patients with mechanical neck pain – a randomized study - Ojoawo, Adesola O.; Ige, Blessing; Kunnuji, Kanode (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Neck pain is becoming increasingly common throughout the world with a considerable impact on individuals. This study compared the effects of muscle energy techniques (MET) and static stretching (SS) on pain intensity and functional disability of patient with mechanical neck pain. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Fifty subjects with mechanical neck pain recruited were randomly allocated into MET and SS groups equally. Subjects in MET received MET protocol, and SS groups were treated with SS; both groups had treatment twice a week for six weeks. Pain intensity and functional disability at baseline, 3rd and 6th week of treatment were measured. Descriptive and Inferential statistics were used to analyze the data. Alpha level was set at <0.05. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. There were 12 males and 13 females for MET with age ranged between 31–53 years mean was 42.41± 7.35 years and 11 males and 14 females in SS group with age range 22–60 years and mean age of 42.91±10.44 years. There was a significant reduction in pain intensity and disability in MET’s and SS group (p<0.05) when pre-treatment, 3rd week and 6th week treatment were compared. Pain intensity was lower at SS than MET while functional disability was lower in MET than SS p<0.05 at 6th week. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. MET reduces ND more than SS and SS reduces pain intensity better MET.